Association between vitamin D status and sepsis in children: A meta-analysis of observational studies. Issue 6 (June 2020) - Xiao, Dongqiong; Zhang, Xiaoyan; Ying, Junjie; Zhou, Yan; Li, Xihong; Mu, Dezhi; Qu, Yi
Summary: Background: The consequences of vitamin D deficiency regarding sepsis in children remain controversial. We conducted a meta-analysis of studies evaluating the association between vitamin D status and sepsis in children. Methods: We used EMBASE, Ovid Medline and Cochrane Library to conduct a meta-analysis of studies published in English before November 21, 2017. Results: Among 1146 initially identified studies, we included 13 studies according to predefined inclusion criteria comprising 975 patients and 770 control participants. According to a random effects model, the mean difference in 25(OH)D levels (nmol/L) between participants with sepsis (444) and controls (528) was (mean difference,  −18.55; 95% confidence interval (CI),  −19.45 to −17.66, p  < 0.05). The association between vitamin D deficiency and sepsis was significant, with an odds ratio (OR) = 1.13 (95% CI, 1.18 to 1.50, p  < 0.05). Factors that could explain differences in the results include the study location/medical conditions, study design, 25(OH)D assay methods, diagnostic sepsis at different ages, diagnostic criteria for sepsis, and sepsis with comorbidities. Conclusions: The association between vitamin D deficiency/lower 25(OH)D levels and sepsis was significant in children and neonates. Further studies are required to confirm the results by considering more confounders.